Method of Applying Metal Powder to the Gate Valve Surface using Laser Technology - Ibragimov, N.Y. (Herald of Azerbaijan Engineering Academy, 2021)
A scheme of the technology for applying metal powder to the surface of the gate valve has been developed. At the same time, the composition of various metal powders is p Based on the obtained dependence the main parameters of the technological process are calculated. Based on this calculation, a metal coating of any thickness can be applied to the gate surface. The performance of these coatings depends on the operating condition, power and pulse of the laser technology. With the help of a laser system, the method of applying metal powder coating on the surface of the gate valve receives a high quality of cleanliness, compared to other installations, the method of applying metal powder coating on the surface of the gate valve resistance resented, depending on the material of the gate steel. Taking into account each composition of a chemical element, a metal powder is prep pared.